MOOC quality design criteria for programming and non-programming students / Aniza Sabjan ... [et al.] - Sabjan, Aniza; Abd Wahab, Alawiyah; Ahmad, Azizah; Ahmad, Rahayu; Hassan, Syahida; Wahid, Juliana (Universiti Teknologi MARA, 2020)
The purpose of this study is to investigate the quality design criteria for developing a Massive Open Online Course (MOOC). Currently, there are limited studies that highlight the required design criteria for the MOOC programming courses. A descriptive analysis was conducted to examine the characteristics of the three important quality design criteria which are (i) Instructional Design Criteria involving Lecture Organization and Culture; (ii) Technical Criteria involving User Interface, Video Content, Learning and Social Tools, and Learning Analytics; and (iii) E-Assessment. The data were collected from 306 respondents, representing the UUM MOOC students of 2018 class, were further analyzed using the T-Test hypothesis testing to determine whether both the programming and nonprogramming students require the same quality design criteria. The questionnaire used in this study consists of 46 items related to the MOOC quality design criteria that were adapted from previous studies. The results indicate that out of the nine constructs, four have obtained significant differences in the mean scores, namely the Video Content, Instructional Design, Culture, and E-assessment. This signifies that different quality design criteria are needed for both the programming and nonprogramming students. The outcome of this study may assist the developers in designing the MOOC by providing the required criteria according to its importance.